2010
DOI: 10.1002/rmv.647
|View full text |Cite
|
Sign up to set email alerts
|

Enteroviruses and type 1 diabetes: towards a better understanding of the relationship

Abstract: Environmental factors, especially viruses, are involved in the initiation or the acceleration of type 1 diabetes (T1D) pathogenesis. Epidemiological data strongly suggest that enteroviruses, such as coxsackievirus B4 (CV-B4), can be associated with T1D. It has been demonstrated that enterovirus infections were significantly more prevalent in at risk individuals, such as siblings of diabetic patients, when they developed anti-beta-cell autoantibodies or T1D, and in recently diagnosed diabetic patients, compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 133 publications
0
52
0
1
Order By: Relevance
“…Type B Coxsackievirus (CV-B) encompassing CV-B 1-6, may be responsible for a large pathological specter varying from benign acute to severe chronic diseases such as chronic myocarditis, dilated cardiomyopathy, and type 1 diabetes. 2 An association between enteroviruses, especially CV-B and type 1 diabetes (T1D) was reported. Enteroviral components have been more frequently detected in blood of T1D patients, and a meta-analysis has reported a strong association between EV detection, especially CV-B, and T1D.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type B Coxsackievirus (CV-B) encompassing CV-B 1-6, may be responsible for a large pathological specter varying from benign acute to severe chronic diseases such as chronic myocarditis, dilated cardiomyopathy, and type 1 diabetes. 2 An association between enteroviruses, especially CV-B and type 1 diabetes (T1D) was reported. Enteroviral components have been more frequently detected in blood of T1D patients, and a meta-analysis has reported a strong association between EV detection, especially CV-B, and T1D.…”
Section: Introductionmentioning
confidence: 99%
“…5 Moreover, experimental studies, in vitro and in vivo animal models, revealed that CV-B4 may be involved in the pathogenesis of T1D through several mechanisms. 2,6,7,8 It has been shown that non-neutralizing anti-CV-B4 IgG obtained from serum of patients can increase the infection of peripheral blood mononuclear cells (PBMC) with CV-B4, which results in production of IFNa and other inflammatory cytokines. 9,10,11,12,13,14 The role of enhancing IgG levels in the outcome of CVB4 infections and other conditions such type 1 diabetes, cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Type B Coxsackievirus infections are generally asymptomatic, but when symptomatic, the pathological specter varies from benign acute infection of the gastrointestinal tract to severe chronic infections such as chronic myocarditis, dilated cardiomyopathy, and type 1 diabetes. 2 Indeed epidemiological data evidenced an association between enteroviruses, especially CV-B and type 1 diabetes (T1D) in genetically predisposed individuals, and experimental studies, in vitro and in vivo in animal models, revealed several mechanisms through which CV-B infection may be involved in the pathogenesis of T1D. [2][3][4][5] Plasma, serum and IgG from CV-B4 E2 seropositive subjects have been shown to strongly increase the CV-B4 E2-induced production of IFNa by human peripheral blood mononuclear cells (PBMCs), in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…2 Indeed epidemiological data evidenced an association between enteroviruses, especially CV-B and type 1 diabetes (T1D) in genetically predisposed individuals, and experimental studies, in vitro and in vivo in animal models, revealed several mechanisms through which CV-B infection may be involved in the pathogenesis of T1D. [2][3][4][5] Plasma, serum and IgG from CV-B4 E2 seropositive subjects have been shown to strongly increase the CV-B4 E2-induced production of IFNa by human peripheral blood mononuclear cells (PBMCs), in vitro. 6,7 That increase was the consequence of an enhancement of the infection of PBMC with CV-B4 E2 by non-neutralizing anti-CV-B4 E2 IgG.…”
Section: Introductionmentioning
confidence: 99%
“…18,19,21 No entanto, a diminuição da frequência de escovagem dentária não pode estar isoladamente associada ao desenvolvimento de lesões de cárie dentária, devido à etiologia multifatorial desta doença. 6,38,39 Apresenta, contudo, um papel preponderante na prevenção do desenvolvimento da cárie dentária e na manutenção de uma boa saúde oral.…”
Section: Controlounclassified